Studying the role of education in eliminating violence against women - Hafiz Muhammad Ather Khan; Riaz Hussain Khan Sindher; Irshad Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The study was conducted with the main objective of analyzing the role of education in eliminating violence against women, and to identifying the nature and forms of violence against women prevailing in the society. The study was delimited to the rural areas of Tehsil Ahmadpur East of district Bahawalpur. The population of the study consisted of married women of 18-60 years age group. Snowball convenient sampling technique was used for data collection. The data was collected by administering self-prepared inventory which was filled as the incident occurred and reported by the informer after cross verification from the locality. The data was collected from both of the population cohorts i.e. urban and rural. The researchers collected data from victims of violence with different levels of education starting from illiteracy to the Masters' level qualification. The collected data were analyzed in terms of percentage according to the qualification of the respondents and were presented in graphical form. The study concluded that violence against women exists in different forms including pushing and soaking, twisting their arms, pulling hair, hit by thrown things on them for injuring or torturing, closing their mouth with hands or some other thing causing suffocation , and beating with wooden stick or iron rod and/ or something like this. The study also concludes that illiterate women had ever experienced one or the other form of physical violence. The occurrence of violence appeared negatively related with level of education of the women. The results demonstrated a significant decrease in physical violence against women with increasing the level of education. Therefore, female education seems necessary for eliminating violence against women and guaranteeing their basic human rights.
Keywords: 330; violence against women; human rights; literacy; socialization; physical violence; domestic violence